Control of porosity in hierarchically porous polymers derived from hyper‐crosslinked block polymer precursors. Issue 8 (5th February 2018) - Kim, Soobin; Seo, Myungeun
ABSTRACT: We report an approach to control the pore characteristics of hierarchically porous polymers (HPPs) containing micropores in a well‐defined 3D continuous mesoporous framework, by the hyper‐crosslinking reaction of a crosslinked block polymer precursor polylactide‐ b ‐poly(vinylbenzyl chloride‐ co ‐styrene‐ co ‐divinylbenzene) (PLA‐ b ‐P(VBzCl‐ co ‐S‐ co ‐DVB)) consisting of bicontinuous PLA and P(VBzCl‐ co ‐S‐ co ‐DVB) microdomains. We investigated the hyper‐crosslinking reaction of P(VBzCl‐ co ‐S‐ co ‐DVB)s synthesized by reversible addition‐fragmentation chain transfer (RAFT) copolymerization, and then examined the effect of VBzCl, S, DVB, and polylactide macrochain transfer agent (PLA‐CTA) contents in the polymerization mixture on the pore characteristics of the HPPs. We demonstrate that while the VBzCl content responsible for the hyper‐crosslinking reaction primarily governs microporosity, the DVB content has a strong influence on the mesopore structure, as it determines the onset of the gelation of the polymerization mixture, which arrests the emerging disordered bicontinuous morphology induced by the polymerization‐induced microphase separation process. Because the PLA microdomains template the percolating mesoporous space, mesoporosity was mainly controlled by the PLA‐CTA contents. The synergistic combination of hyper‐crosslinking and block polymer self‐assembly in the HPP formation provided a highly reinforced mesoporous framework, stable against pore collapse, and interconnected mesopores. These facilitated diffusion to the microporous surfaces, suggesting its utility for advanced absorbents and catalytic supports. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 900–913 Abstract : A marriage of hyper‐crosslinking reaction and polymerization‐induced microphase separation process produces hierarchically porous polymer‐containing micropores generated by the hyper‐crosslinking within the mesoporous wall templated by the block copolymer self‐assembly. Pore characteristics of the hierarchically porous polymer can be readily tuned by adjusting composition of the polymerization mixture. The hierarchically porous polymer exhibits improved mesopore stability and facilitated diffusion to microporous surface, indicating synergistic enhancement stemmed from the hierarchical pore structure.